The Juxtaposed Object of the Social Sciences and Its Implications in Teacher Training - Cuesta-Moreno, Óscar Julián; Meléndez-Labrador, Sandra Mireya (Revista Electrónica Educare, 2022)
Objective. To analyze the debate on the construction of the object of the social sciences and its implications in the training of teachers. Discussion. At first, a conceptualization of the social sciences is proposed by defending the juxtaposed ontology of its object; likewise, epistemological and methodological considerations are debated in terms of totality. Then, it is reflected on the place of the subject who practices the social sciences and its consequences in the production of knowledge. Finally, considerations are raised on the training of teachers in social sciences. Conclusions. The curricular design to train teachers in social sciences must go through the construction of spaces that lead to two actions: first, to problematize aspects of reality without being reduced to compartmentalization of the departments; and second, to generate an epistemological awareness that leads them to account for their order of intellection or policies of interpretation in the production of knowledge.